What difference could in-service training make? Insights from a public school of Pakistan. Issue 1 (1st January 2017) - Nawab, Ali
Abstract : In-service courses have been used as a common strategy to build the capacity of teachers to meet the constantly changing demands of modern schooling. But how the teachers implement the ideas and strategies acquired from such in-service training and what conditions influence the implementation process is the least examined area in Pakistan, especially in the rural context. Using a case study approach, the current study explored the possibilities and challenges of implementing strategies, learnt through in-service training, in a public school in rural Pakistan. It was found that in-service courses have a positive impact upon the attitude and practices of the trainee teacher. However, due to various structural and cultural barriers, the teacher is not able to implement many of the strategies and ideas in the school context. The hierarchical structure of schools, teachers' workload, lack of resources and insufficient support from colleagues and management hinder the process of implementation. The study suggests that in-service training should provide the trainees with ideas and skills to cope with the structural and cultural challenges at school. Moreover, ongoing support and encouragement from colleagues, course facilitators and management is required to sustain the implementation of strategies learnt during training.